USING ARTIFICIAL INTELLIGENCE IN EDUCATION 4.0 - UDVAROS, Jozsef; FORMAN, Norbert (Journal of Technology and Information Education, 2023)
Education 4.0 is a new educational paradigm that aims to address the needs and opportunities of Industry 4.0. The paradigm allows students to determine their own model and pace of learning. Education 4.0 is based on the concept of learning by doing, in which students are encouraged to learn and discover different things in an experimental, unique way. Despite the fact that the possibilities offered by Education 4.0 excite the imagination of more and more people, the level of implementation and support is still in the very early stages, although in some parts of the world we can already find smaller and larger attempts, but these are still mostly running on a test basis. In Education 4.0, Artificial Intelligence (AI) can play a key role in identifying new factors influencing student performance and implementing personalized learning, answering routine student questions, using learning analytics and predictive modelling. A new challenge is to redefine Education 4.0 to recognize creative and innovative intelligent students, and it is difficult to define student outcomes. This article presents how Artificial Intelligence combined with machine learning creates a constructive relationship between the student and the instructor, what AI-driven tools exist to implement this, how AI can be useful for individual development, and how it can effectively collaborate with the instructor in order to ensure that the student receives the best education. Key words: Artificial Intelligence, Education 4.0, AIED
Keywords: Artificial Intelligence; Education 4.0; AIED